Sensory and technological properties of developed functional bread enriched by microencapsulated fish oil - Hasani, Shirin; Ojagh, Seyed Mahdi; Hasani, Maryam; Ghorbani, Mohammad (Progress in Nutrition, 2019)
The object of this study was to develop functional bread enriched with omega-3 fatty acids. Therefore, to produce enriched bread, fish oil containing long-chain omega-3 polyunsaturated fatty acids was microencapsulated with different wall material component [chitosan (CS) and modified starch (Hi-cap 100)] by freeze drying. Then, the size and stability of the emulsion droplet, viscosity and the properties of the microencapsulated powders after freeze drying were determined. The combination of CS: Hi-cap 100 (1%: 9%) as best formulation of wall component in fish oil microcapsules was then incorporated in to bread to develop functional properties. Results indicated that enriched bread with 5% microencapsulated fish oil, had the highest value in firmness, crust and color of bread. In addition, Sensory results showed that there was no significant difference between enriched with 1% fish oil microcapsules and control on texture, appearance and crumb. So, Using of microencapsulated fish oil as an effective additive for improvement of nutritional value of semi volume bread and its application is suggested for production of other bakery products.